Anthropogenic land-use stress alters community concordance at the river-riparian interface. (June 2016) - Tonkin, Jonathan D.; Stoll, Stefan; Jähnig, Sonja C.; Haase, Peter
Highlights: Concordance across ecotones including the river-riparian interface remain uncertain. Community structure, but not richness, was highly concordant between all groups. Anthropogenic stress reduced linkages between riparian spiders and carabid beetles. Concordance between plants and other groups increased with anthropogenic stress. Differences in concordance patterns arose through two contrasting mechanisms. Abstract: Organisms often respond in similar ways to environmental or spatial gradients, particularly at large spatial scales. Yet, while understanding these relationships is important for both basic and applied purposes, such as identifying surrogate taxa for conservation and monitoring purposes, patterns at finer scales and across ecotones are less certain. Our central aim was to explore patterns in community concordance at the river-riparian interface and examine whether concordance was decoupled by increasing anthropogenic stress (a gradient of local land-use intensity). We explored this at 15 sites over three years within the LTER site, Rhine-Main-Observatory, a low mountain river system in central Germany, assessing concordance between four organism groups: riparian spiders and carabid beetles, benthic macroinvertebrates, and combined aquatic macrophytes and riparian plants. This represented three different linkages: (1) predator–prey, (2) direct competition, and (3) habitat associations. While there were no correlations in richness patterns, multivariate community structure was highly concordant between all groups. Anthropogenic stress strongly reduced links between riparian spiders and carabid beetles, likely resulting from their shared resource requirements. However, increasing concordance generally occurred between plants and other groups, although inconsistently between the three groups. We posit that patterns may be resulting from two processes: (1) linkages between directly competing species decouple with increasing anthropogenic stress, and (2) stronger coupling may occur between habitat providers and dependent species when overall habitat complexity is reduced. Our results highlight the complex manner in which anthropogenic stress can influence ecosystem structure, particularly at small scales. Based on these complexities, we recommend considering the full suite of community data to adequately explore biodiversity patterns or when searching for surrogate taxa.